2020
DOI: 10.36416/1806-3756/e20190221
|View full text |Cite|
|
Sign up to set email alerts
|

EBUS-TBNA versus surgical mediastinoscopy for mediastinal lymph node staging in potentially operable non-small cell lung cancer: a systematic review and meta-analysis

Abstract: Objetivo: O câncer de pulmão (CP) é uma das principais causas de morte no mundo. Um estadiamento mediastinal preciso é obrigatório para avaliação do prognóstico e seleção de pacientes para tratamento cirúrgico. EBUS-TBNA é um procedimento minimamente invasivo que permite a amostragem de linfonodos mediastinais. Alguns estudos sugerem que a EBUS-TBNA é preferível que a mediastinoscopia cirúrgica no estadiamento mediastinal do CP. O objetivo desta revisão sistemática e meta-análise foi comparar a eficácia da EBU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…EBUS-TBNA has become a mature interventional diagnostic procedure in clinical practice. Previous studies showed that no statistically signi cant difference was identi ed between EBUS-TBNA and mediastinoscopy in diagnostic sensitivity to evaluate malignant lymph nodes with previous imaging results indicating the enlargement of mediastinal and/or hilar lymph nodes or adjacent lesions in lungs (Figueiredo et al 2020). However, compared to mediastinoscopy, EBUS-TBNA was a less invasive procedure with low costing and better tolerability for patients (Sampsonas et al 2018;Verdial et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…EBUS-TBNA has become a mature interventional diagnostic procedure in clinical practice. Previous studies showed that no statistically signi cant difference was identi ed between EBUS-TBNA and mediastinoscopy in diagnostic sensitivity to evaluate malignant lymph nodes with previous imaging results indicating the enlargement of mediastinal and/or hilar lymph nodes or adjacent lesions in lungs (Figueiredo et al 2020). However, compared to mediastinoscopy, EBUS-TBNA was a less invasive procedure with low costing and better tolerability for patients (Sampsonas et al 2018;Verdial et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…This P r e p r i n t 11 misclassified percentage was more than 50% for the left lower paratracheal LNs. Such problem was further studied by EBUS-TBNA, which was recognized as the most diagnostic value in hilar/mediastinal (N1/N2) lymph node staging [17][18][19]. The concordance between these two maps for the left side LNs was poor (Kappa 0.374).…”
Section: Discussionmentioning
confidence: 99%
“…EBUS-TBNA has become a mature interventional diagnostic procedure in clinical practice. Previous studies have found no statistically significant difference in diagnostic sensitivity between EBUS-TBNA and mediastinoscopy for malignant lymph nodes evaluations, in cases where previous imaging results have indicated enlargement of mediastinal and/or hilar lymph nodes or adjacent lesions in the lungs [ 16 ]. However, compared to mediastinoscopy, EBUS-TBNA is less invasive, less expensive, and more tolerable for patients [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%